Dari wisata bahari menuju ekowisata berkelanjutan: Valuasi ekonomi Pantai Ngudel melalui pendekatan CVM dan TCM - Saifudin Zuhri; Muhammad Adi Adrian (Journal of Economics Research and Policy Studies, 2026)
Ngudel Beach in Sindurejo Village, Gedangan District, Malang Regency, holds significant potential for development as an ecotourism area; however, it still faces limitations regarding facilities, low community involvement, and a lack of information on the area's economic value. This study aims to analyze the baseline state of community participation and estimate the economic value of Ngudel Beach using the Contingent Valuation Method (CVM) and the Travel Cost Method (TCM). Primary data were obtained through a survey of 253 tourists using purposive sampling between February and June 2026. The results indicate that 93% of respondents were willing to pay an additional fee (ecotourism fee), with an average willingness-to-pay (WTP) of IDR 13,000 per person; consequently, the potential economic value based on CVM is estimated at IDR 2.555 billion per year. TCM analysis revealed an average travel cost of IDR 727,016 per person per visit, with a total potential economic value reaching IDR 46.54 billion per year. These findings demonstrate a positive economic preference among tourists for developing Ngudel Beach into a sustainable ecotourism area, as well as the importance of improving facilities and strengthening community participation in the area's management.